Parallel-Distinct Structures of Internal World and External Reality: Disavowing and Re-Claiming the Self-Identity in the Aftermath of Trauma-Generated Dissociation - Şar, Vedat (Frontiers in Psychology, 2017)
The nature of consciousness and the autonomy of the individual’s mind have been a focus of interest throughout the past century and inspired many theories and models. Revival of studies on psychological trauma and dissociation, which remained outside mainstream psychiatry, psychology, and psychoanalysis for the most part of the past century, has provided a new opportunity to revisit this intellectual and scientific endeavour. This paper attempts to integrate a series of empirical and theoretical studies on psychological consequences of developmental traumatization, which may yield further insight into factors which threaten the integrity of human consciousness. The paper proposes that an individual’s experience of distorted reality and betrayal precipitates a cyclical dynamic between the individual and the external world by disrupting the developmental function of mutuality which is essential for maintenance of the integrity of the internal world while this inner world is in turn regulated vis-à-vis external reality. Dissociation -the common factor in all types of post-traumatic syndromes- is facilitated by violation of boundaries by relational omission and intrusion as represented by distinct effects and consequences of childhood neglect and abuse. Recent research conducted on clinical and non-clinical populations shows both bimodal (undermodulation and overmodulation) and bipolar (intrusion and avoidance) neurobiological and phenomenological characteristics of post-traumatic response. These seem to reflect “parallel-distinct structures” that control separate networks covering sensori-motor and cognitive-emotional systems. This understanding provides a conceptual framework to assist explanation of diverse post-traumatic mental trajectories which culminate in a common final pathway comprised of partly overlapping clinical syndromes such as complex PTSD, dissociative depression, dissociative identity disorder, or “borderline” phenomena. Of crucial theoretical and clinical importance is that these maladaptive post-traumatic psychological formations are regarded as processes in their own right rather than as a personality disorder innate to the individual. Such mental division may perform in that internal detachment can serve to preserve the genuine aspects of the subject until such time as they can be reclaimed via psychotherapy. The paper attempts to integrate these ideas with reference to the previously proposed theory of the “Functional Dissociation of Self” (Şar and Öztürk, 2007).